Temperature Variation during Salt Migration in Frozen Hydrate-Bearing Sediments: Experimental Modeling - Evgeny Chuvilin; Valentina Ekimova; Dinara Davletshina; Boris Bukhanov; Ekaterina Krivokhat; Vladimir Shilenkov (Geosciences, 2022)
Salt migration may be another reason why pore-gas hydrates dissociate in permafrost, besides pressure and temperature changes. Temperature variations in frozen hydrate-saturated sediments interacting with a NaCl solution have been studied experimentally at a constant temperature, ~−6 °C typical for permafrost. The experiments with frozen sandy samples containing metastable methane hydrate show that the migration of Na+ ions in the NaCl solution and their accumulation in the sediments can induce heat-consuming hydrate dissociation and ice melting. The hydrate-saturated frozen soils cool down at higher rates than their hydrate-free counterparts and require more time to recover their initial temperature. The temperature effects in hydrate-saturated frozen sediments exposed to contact with NaCl solutions depend strongly on salt concentration. The experimental results are used to model phase changes in the pore space associated with salt-ions transport and provide insights into the reasons for temperature changes.